Electrically controlled spin angular momentum of light through lithium niobate domain engineering - Chao Zhou; Xuejing Cui; PengCheng Chen; Xiaoyi Xu; Zhilin Ye; Yawen Su; Yue Wu; Xiaopeng Hu; Shining Zhu; Min Xiao; Yong Zhang (Physical Review Research)
The investigations of spin angular momentum (SAM) of light have demonstrated many interesting photonic-spin-dependent effects. However, it is still a great challenge to manipulate a photonic SAM state in a designable and dynamic way. Here we propose to electrically control the SAM of light through lithium niobate (LN) domain engineering. In our design, each unit cell consists of a pair of positive and negative domains, which introduces a spin-dependent geometric phase. One can feasibly tune such geometric phase by applying an electric field. After properly arranging LN domains, we have successfully achieved a designed geometric phase distribution for electrically controlled separation of photonic SAM states. Our work paves the way to dynamically manipulate the SAM of light for high-speed beam steering, switchable wave front shaping, and dynamic holography.